THE ROLE OF THE FINANCIAL SERVICES AUTHORITY (OJK) IN PROTECTING FINTECH P2P LENDING CUSTOMERS FROM THE PERSPECTIVE OF MAQASHID SYARI'AH - Farhan Akbar; Ida Friatna; Riadhus Sholihin (JURISTA: Jurnal Hukum dan Keadilan, 2025)
This research examines the role of the Financial Services Authority (OJK) in protecting fintech Peer-to-Peer (P2P) lending customers in Aceh from a maqashid sharia perspective. P2P lending services, which are part of the development of financial technology (fintech), have proliferated in Aceh as an alternative financing solution that is faster and more flexible than conventional financial institutions. However, this growth also presents new risks, especially to consumer protection. This research employs a descriptive qualitative approach, utilizing interviews, literature reviews, and observational methods. The results show that OJK has made various efforts to supervise fintech P2P lending, including through regulations, digital monitoring systems, and public education. From the perspective of maqashid sharia, the protection carried out by OJK against customers reflects efforts to protect the soul (hifz al-nafs) and property (hifz al-mal), which are part of the primary objectives of Islamic law. Based on the analysis, the author considers that OJK's role in supervising and protecting fintech P2P lending customers has shown significant alignment with the principles of maqashid sharia, especially in the aspects of hifzh al-nafs (guarding the soul) and hifzh al-mal (guarding wealth).